A Randomized, Double‐Blind, Placebo‐Controlled, Multicenter Study of Rabbit ATG in the Prophylaxis of Acute Rejection in Lung Transplantation. Issue 5 (11th March 2014) - Snell, G. I.; Westall, G. P.; Levvey, B. J.; Jaksch, P.; Keshavjee, S.; Hoopes, C. W.; Ahya, V.; Mehta, A.; Trulock, E. P.; ,
<x xml:space="preserve">Abstract</x> ATG‐Fresenius S (ATG‐F) is a polyclonal anti‐human‐T‐lymphocyte immunoglobulin preparation that has been clinically developed to prevent episodes of acute cellular rejection. This study evaluated the efficacy and safety of ATG‐F at doses of 5 and 9 mg/kg versus placebo in adult recipients of a primary lung allograft. The primary efficacy composite end point was defined as death, graft loss, acute rejection and/or loss to follow‐up within 12 months of transplantation. The interim analysis showed the ATG‐F 5 mg/kg treatment to be inefficacious, and it would be impossible to enroll enough patients to power the study to show a difference between the 9 mg/kg arm and the placebo arm. Therefore, the main focus of the study shifted to the safety end points and a descriptive analysis of the primary end point. At 12 months posttransplant, the efficacy failure rate was not significantly different between the ATG‐F 9 mg/kg group and the placebo group (40.2% vs. 36.7%, respectively). This large study did not demonstrate a significant reduction in acute cellular rejection, graft loss or death with single‐dose induction therapy with ATG‐F within the first year after lung transplantation.